Endurance running in Europe: Decline and fall? - Butcher, P. (New Studies in Athletics, 2007)
It is fashionable to blame the rise of African runners for the decline of endurance running in Europe but, in fact, there are a number of reasons for the fall off that are more local in nature. Drawing on personal experience and conversations with several successful coaches, the author identifies possibilities from both a British and European perspective. The modern lifestyle of young Europeans, a decline in schools athletics, changes in the training of grass roots athletes following the running boom of the 1980s and a reduction in the exchange of ideas between coaches are among the ideas explored. Turning to ways to address the situation, he examines the approach of rising star Mohammed (Mo) Farah (GBR) and examples of best practice from the USA, where a resurgence in the level of performance has included medals in both men`s and women`s marathons at the 2004 Olympic Games in Athens.